Demonstration of the healthy worker survivor effect in a cohort of workers in the construction industry. Issue 12 (1st December 2001) - Siebert, U; Rothenbacher, D; Daniel, U; Brenner, H
Abstract : OBJECTIVES: To assess the potential of a healthy worker survivor effect due to differential occupational mobility in a cohort of construction workers. METHODS: A cohort of 10 809 male employees in the German construction industry aged 15–64 years was followed up for occupational mobility, early retirement due to permanent disability, and total mortality from 1986 to 1994. Using the Cox's proportional hazards model of relative rates (RRs) with 95% confidence intervals (95% CIs) of occupational mobility, early retirement and total mortality were estimated according to medical diagnoses at baseline after adjustment for various covariates. RESULTS: During follow up, 2472 subjects changed employment, 359 employees were granted a disability pension for health reasons and 188 subjects died. A wide range of chronic diseases was associated with increased rates of early retirement and total mortality but not occupational mobility. However, a healthy worker survivor effect was identified related to disorders of the back and spine (ninth revision of the international classification of diseases, ICD-9, code 720-4), a common predictor of both occupational mobility (RR 1.17, 95% CI 1.04 to 1.32) and early retirement (RR 1.50, 95% CI 1.20 to 1.88). In total, there were about as many events of occupational changes (n = 41) as events of early retirement due to permanent disability (n = 39) significantly attributable to disorders of the back and spine. Differential occupational mobility preceded differential early retirement due to permanent disability by more than one decade. CONCLUSIONS: These findings show the need to consider a healthy worker survivor effect due to occupational mobility in occupational epidemiological research. Furthermore these results underline the necessity of further health promotion targeting work related conditions in the construction industry.